Rekonstruksi Kepemimpinan Pendidikan Umar bin Abdul Aziz: Aktualisasi Politik Pengembangan Pendidikan - Yusuf Hanafiah (STAI Terpadu Yogyakarta, 2021)
The article aims to explore the politics of education at Umar bin Abdul Aziz's time and then reconstruct it with the realities of contemporary education. In examining this, the author uses qualitative methods with the type of research library. The search results show that Umar bin Abdul Aziz developed an educational aspect focusing on three areas, namely 1) family education, 2) formal education, and 3) community education. These three development fields are still very relevant if reconstructed and contextualized with current education development.